A Case Report of Kienbock’s Disease with Distal Radioulnar Joint Dislocation - Chusing, MD, Natdanai (Journal of Southeast Asian Orthopaedics, 2022)
Kienbock’s disease is known as osteonecrosis of the lunate. The cause is unknown, but several theories endeavor to explain such as mechanical and vascular theories. Kienbock’s disease can lead to collapse and fracture of the lunate and eventually collapse of proximal carpal row and progress to arthritis of the adjacent joints. This report presents the case of a 62-year-old female patient with Kienbock’s disease combined with distal radioulnar joint dislocation, nowadays not yet reported as the cause of Kienbock’s disease.